African-American Males in Higher Education - Cedric G. Sanders (Adult Education Research Conference, 2017)
The purpose of this roundtable proposal is to present and frame a future research project challenging the narrative of disparity on African-American males in higher education and advocate the need for scholarship that focuses on positive stories of how African-American males navigate in higher education.
Keywords: African-American males; Higher education; Transformative; Barriers; Positive